Composition in the university : historical and polemical essays - Crowley, Sharon, 1943- (Pittsburgh series in composition, literacy, and culture., 1998)
Composition in the University examines the required introductory course in composition within American colleges and universities. Crowley argues that due to its association with literary studies in English departments, composition instruction has been inappropriately influenced by humanist pedagogy and that modern humanism is not a satisfactory rationale for the study of writing. Crowley envisions possible nonhumanist rationales that could be developed for vertical curricula in writing instruction, were the universal requirement not in place. Composition in the University examines the requi.